2013
DOI: 10.1371/journal.pone.0074411
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Selenium Incorporated Guar Gum Nanoparticle and Its Interaction with H9c2 Cells

Abstract: This study deals with the preparation and characterization of selenium incorporated guar gum nanoparticle (SGG), and its effect on H9c2 cardiomyoblast. Herein, nanoprecipitation techniques had been employed for the preparation of SGG nanoparticle. The prepared nanoparticle had been subjected to various types of analytical techniques like transmission electron microscopy (TEM), X-ray diffraction (XRD) and particle size analysis to confirm the characteristics of nanoparticle as well as for selenium incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…4c and d, which were consistent with a previous report demonstrating that CS was conjugated to SeNPs through −OH groups (Yu et al, 2012). Further supports for the above conclusion comes from recent studies showing that selenium was prone to interacted with O-and N-containing groups by forming Se-O and Se-N bonds, consequently stabilizing selenium nanoparticles by other dispersants Soumya et al, 2013). In sum, the synthesis of CS-SeNPs might begin with an attack of the precursor, SeO 3 2− by the amino groups of CS because of electrostatic effects.…”
Section: Cs (L)-senps (A) and Cs (H)-senps (B) At The Initial Stage Asupporting
confidence: 90%
See 1 more Smart Citation
“…4c and d, which were consistent with a previous report demonstrating that CS was conjugated to SeNPs through −OH groups (Yu et al, 2012). Further supports for the above conclusion comes from recent studies showing that selenium was prone to interacted with O-and N-containing groups by forming Se-O and Se-N bonds, consequently stabilizing selenium nanoparticles by other dispersants Soumya et al, 2013). In sum, the synthesis of CS-SeNPs might begin with an attack of the precursor, SeO 3 2− by the amino groups of CS because of electrostatic effects.…”
Section: Cs (L)-senps (A) and Cs (H)-senps (B) At The Initial Stage Asupporting
confidence: 90%
“…Many efforts have been made to stabilize the red selenium particles including the use of proteins (Kaur, Iqbal, & Bakshi, 2009;Shirazi et al, 2014;Xia, 2007), polyphenols (Barnaby, Sarker, Dowdell, & Bannerjee, 2011;Pi et al, 2013;Wu et al, 2013), polysaccharides (Kong et al, 2014;Soumya, Vineetha, Reshma, & Raghu, 2013;Zheng et al, 2013), melatonin , ATP , and monosaccharides (Zheng et al, 2011). These all have been used as dispersants to prepare stable and uniform selenium nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of H9C2 cells to certain chemicals for 24 hrs leads to apoptosis [8]. Treatment with 100 nM sodium selenite and SeNPs are effective in protecting the cells from apoptosis at 24 hrs and this property of selenium and its nanoparticles indicate their potential usefulness as a therapeutic agent against cardiomyopathy ( Figure.8).…”
Section: Selenium and Senps Protect The Cells From Apoptosismentioning
confidence: 99%
“…Over the past decade, much effort had been devoted to synthesize and stabilize SeNPs with the use of polysaccharides, 15,[18][19][20] monosaccharides, 21 proteins, 3,[22][23][24] amino acids, 25 polyphenols, [26][27][28] melatonin, 29 ATP, 30 complex plant extract 10,31 and even microorganism culture. 8 Among them, polysaccharide is regarded as an appropriate template for fabricating SeNPs when considering energy efficiency and eco-friendliness, according to Zhang et al 15 However, the SeNPs prepared using polysaccharides were found to be unstable, due to enlargement of size and decrease of zeta potential during storage in aqueous environment.…”
mentioning
confidence: 99%